Efektifitas Metode Job Instruction Training dan Visual Presentations dalam Pelatihan Tukang Bangunan Menerapkan Teknologi Ferosemen - Gunasti, Amri; Sanosra, Abadi; Muhtar, Muhtar; Ipak Rahmawati, Erna (Sustainable Civil Building Management and Engineering Journal, 2024)
Increasing the ability of builders to apply ferrocement technology as a building material is a very urgent activity. The use of visual presentations that represent Off the job training methods and job instruction training that represent On the job training as training methods for builders needs to be further investigated for their level of effectiveness. This research was conducted to measure the effectiveness of the two training methods using different tests. The aim of this research is to determine the effectiveness of the visual presentation method compared to job instruction training. The results of the research show that there are real differences in the indicators of skilled builders stripping plaster, skilled builders installing woven wire stands and knowing their sizes, skilled builders installing woven wire, skilled builders installing binding wire, understanding the sequence of implementation and understanding every detail. the size of each step in implementing ferrocement technology. The research results also stated that there was no difference in the ability indicators for Skilled Builders to Install Plaster using the Visual Presentations or Job Instruction Training methods.